Digitalis metabolism and human liver alcohol dehydrogenase. - Frey, W A (1980)
Human liver alcohol dehydrogenase (alcohol: NAD" oxidoreductase, EC 1.1.1.1) catalyzes the oxidation of the 3 beta-OH group of digitoxigenin, digoxigenin, and gitoxigenin to their 3-keto derivatives, which have been characterized by high performance liquid chromatography and mass spectrometry. These studies have identified human liver alcohol dehydrogenase as the unknown NAD(H)-dependent liver enzyme specific for the free hydroxyl group at C3 of the cardiac genins; this hydroxyl is the critical site of the genins' enzymatic oxidation and concomitant pharmacological inactivation in humans. Several kinetic approaches have demonstrated that ethanol and the pharmacologically active components of the digitalis glycosides are oxidized with closely similar kcat/Km values at the same site on human liver alcohol dehydrogenase, for which they compete. Human liver alcohol dehydrogenase thereby becomes an important biochemical link in the metabolism, pharmacology, and toxicology of ethanol and these glycosides, structurally unrelated agents that are both used widely. Both the competition of ethanol with these cardiac sterols and the narrow margin of safety in the therapeutic use of digitalis derivatives would seem to place at increased risk those individuals who receive digitalis and simultaneously consume large amounts of ethanol or whose alcohol dehydrogenase function is impaired.